The Application of The Movement Education Model to Improve The Basic Movement Skills of Students with Mild Intellectual Disabilities - Kiki Rahayu Widianingsih; Suherman Slamet; Wulandari Putri (Universitas Negeri Semarang, 2025)
This study aims to examine the effectiveness of the Movement Education Model in improving basic movement skills among students with mild intellectual disabilities. The research employed a quasi-experimental design using a one-group pretest-posttest model, involving six students from Special Education Schools Satria Galdin, Bandung Regency. The intervention was conducted over 12 sessions, applying the Movement Education Model based on four core components: body awareness, space, effort, and relationships. Basic motor skills were assessed using the Test of Gross Motor Development–3 (TGMD-3), with data analyzed using a paired sample t-test. Results showed a significant improvement in students’ basic motor skills (pre-test mean = 72.00; post-test mean = 113.83; sig. = 0.001), indicating that the Movement Education Model is effective in developing locomotor and manipulative abilities. These findings support the use of exploratory, individualized, and adaptive physical education models to enhance gross motor development in students with mild disabilities. The study recommends wider implementation of this model in Special Education Schools to support inclusive and equitable physical education practices.